Tyrosine as a Mechanistic-Based Biomarker for Brain Glycogen Decrease and Supercompensation With Endurance Exercise in Rats: A Metabolomics Study of Plasma - Matsui, Takashi; Liu, Yu-Fan; Soya, Mariko; Shima, Takeru; Soya, Hideaki (Frontiers in Neuroscience, 2019)
Brain glycogen, localized in astrocytes, produces lactate as an energy source and/or a signal factor to serve neuronal functions involved in memory formation and exercise endurance. In rodents, 4 weeks of chronic moderate exercise-enhancing endurance and cognition increases brain glycogen in the hippocampus and cortex, which is an adaption of brain metabolism achieved through exercise. Although this brain adaptation is likely induced due to the accumulation of acute endurance exercise–induced brain glycogen supercompensation, its molecular mechanisms and biomarkers are unidentified. Since noradrenaline synthesized from blood-borne tyrosine activates not only glycogenolysis but also glycogenesis in astrocytes, we hypothesized that blood tyrosine is a mechanistic-based biomarker of acute exercise–induced brain glycogen supercompensation. To test this hypothesis, we used a rat model of endurance exercise, a microwave irradiation for accurate detection of glycogen in the brain (the cortex, hippocampus, and hypothalamus), and capillary electrophoresis mass spectrometry–based metabolomics to observe the comprehensive metabolic profile of the blood. Endurance exercise induced fatigue factors such as a decrease in blood glucose, an increase in blood lactate, and the depletion of muscle glycogen, but those parameters recovered to basal levels within 6 h after exercise. Brain glycogen decreased during endurance exercise and showed supercompensation within 6 h after exercise. Metabolomics detected 186 metabolites in the plasma, and 110 metabolites changed significantly during and following exhaustive exercise. Brain glycogen levels correlated negatively with plasma glycogenic amino acids (serine, proline, threonine, glutamate, methionine, tyrosine, and tryptophan) (r < −0.9). This is the first study to produce a broad picture of plasma metabolite changes due to endurance exercise–induced brain glycogen supercompensation. Our findings suggest that plasma glycogenic amino acids are sensitive indicators of brain glycogen levels in endurance exercise. In particular, plasma tyrosine as a precursor of brain noradrenaline might be a valuable mechanistic-based biomarker to predict brain glycogen dynamics in endurance exercise.